The effect of site geometry, Ti content and Ti oxidation state on the Ti K-edge XANES spectrum of synthetic hibonite. (15th August 2016) - Doyle, P.M.; Berry, A.J.; Schofield, P.F.; Mosselmans, J.F.W.
Abstract: The Al-rich oxide hibonite (CaAl12 O19 ) is modeled to be the second mineral to condense from a gas of solar composition and is found within calcium–aluminum-rich inclusions and the matrix of chondritic meteorites. Both Ti 3+ and Ti 4+ are reported in meteoritic hibonite, so hibonite has been proposed as a single mineral oxybarometer that could be used to elucidate conditions within the first 0.2 Myrs of the Solar System. Synthetic hibonites with Ti 3+ /(Ti 3+  + Ti 4+ ) (hereafter Ti 3+ /ΣTi) ranging between 0 and 1 were prepared as matrix-matched standards for meteoritic hibonite. The largest yield of both Ti-free and Ti-bearing hibonite at ∼1300 and ∼1400 °C was obtained by a single sinter under reducing conditions. In situ micro-beam Ti K-edge X-ray absorption near edge structure (XANES) spectra were recorded from the synthetic hibonites, as well as from terrestrial hibonite. Spectral features in the post-crest region were shown to correlate with the Ti 4+ content. Furthermore, Ti 4+ on the M2 trigonal bipyramidal and the adjoining M4 octahedral sites appears to cause variability in the post-crest region as a function of orientation. For this suite of synthetic hibonites it was observed that the pre-edge peak region is not influenced by orientation, but is controlled by Ti 3+ /ΣTi, site geometry and/or Ti concentration. In particular, the pre-edge peak intensities reflect Ti coordination environment and distortion of the M4 octahedral site. Therefore, although pre-edge peak intensities have previously been used to determine Ti 3+ /ΣTi in meteoritic minerals, we excluded use of the pre-edge peak intensities for quantifying Ti valence states in hibonite. The energy of the absorption edge at a normalized intensity of 0.8 ( E 0.8 ) and the energy of the minimum between the pre-edge region and the absorption edge ( E m1 ) were found to vary systematically with Ti 3+ /ΣTi. Ti 3+ /ΣTi in hibonite as a function of E m1 was modeled by a quadratic function that may be used to quantify Ti 3+ /ΣTi in meteoritic hibonite when the synthetic hibonite standards are crystal-chemically matched to the natural samples and are measured during the same analytical session as the meteoritic hibonites.